«STRES MENADŽMENT» - INTERES SVAKE ORGANIZACIJE - Đorđe Mačvanin (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
We live at the time of faster, unpredictable changes. Many factors influence the speed of changes, as well as they form the organization culture. Stress is present all around us as a part of our daily lifes and can not be comple- tely avoided. However, it could be controled, analyzed and prevented. Therefore indivi- dual and organizational strategies for stress elimination, changes and minimization of the stressors represent the key for successfull risk management.